Apresentais os fatos, ensinais a efetuar o mundo : as cartas de Parker em Sergipe (1912-1953) - Santana, Adriana Menezes de (2015)
This work has as study object the Parker charters, school materials focused on discipline arithmetic. The research aims to investigate the movement of such materials that have contributed to the modernization of the teaching of this discipline. The time frame begins in 1912, year of the new organization of primary education in Sergipe, and the final milestone is the year 1953, referred to the dating of the latest report of the education inspector found. To prepare this study, I adopted the evidentiary paradigm in order to dialogue with bibliographic and documentary sources: laws, decrees, messages, educational programs, magazines, in addition to Parker works. Also articulated the evidence located to the concepts of school culture (FELGUEIRAS, 2010b), culture school material (FELGUEIRAS, 2010b), school materials (CARVALHO, 2011), school discipline (Chervel, 1990) and circulation (CHARTIER, 1990), to elucidate this aspect of school material culture in Sergipe, in the fields of history of mathematics education and the history of school subjects.